Strategic position of Dormani hotel in Kuching / Salasmi Sepawie - Sepawie, Salasmi; Ibrahim, Alifah (2010)
Dormani Hotel is one of the new hotels in Kuching owned and managed by bumiputeras. Dormani Hotel is a small hotel with seventy security rooms and was opened in July 2008. Being a new small hotel in hotel industry with many competitors ranging from five-star hotels to cheap lodgings is not an easy task. In addition to that, in order to survive in business, stay profitable and be successful it is essential to determine the strategic position and to establish a competitive advantage. This study was carried out to evaluate and determine strategic position of Dormani Hotel in strategic planning context by conducting strategic analysis. EFE, IFE, CPM and SWOT analysis was conducted by using tools as described by Fred David, 2009. External Audit was performed by using External Factors Evaluation or EFE to identify the opportunities and threats for Dormani Hotel and evaluate how well the hotel performs in the industry and how effectively its current strategies respond to its opportunities and threats. External Audit was also performed by using Competitive Profile Matrix or CPM to carry out comparative analysis in order to evaluate and determine Dormani Hotel's strategic position in Kuching. Dormani Hotel was compared against its benchmarked hotel that is Grand Margherita Hotel and its peers such as Hotel Grand Continental and Harbour View Hotel. Internal Audit was performed by using Internal Factors Evaluation or IFE to identify Dormani Hotel’s strengths and weaknesses and to evaluate the strength of its internal position. In performing External Audit, focus group interview was conducted to assist in identifying critical success factors for hotel in hotel industry. Focus group participants were people invited from various agencies in order to obtain reliable critical factors for success from people involved in the industry. The External Factors Evaluation (EFE) and Competitive Profile Matrix (CPM) for Dormani Hotel were then evaluated by the focus group. Questionnaires were also distributed to few selected five-star hotel, four star hotel and travel agents in Kuching to evaluate and determine strategic position of Dormani Hotel.